2021
DOI: 10.1155/2021/5523726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Warm Acupuncture Combined with Bone Marrow Mesenchymal Stem Cells Transplantation on Cartilage Tissue in Rabbit Knee Osteoarthritis

Abstract: The current study was designed to investigate the effect and underlying mechanism of warm acupuncture combined with bone marrow mesenchymal stem cells (BMSC) transplantation on cartilage tissue injury in rabbit knee osteoarthritis (KOA). In the study, 50 rabbits were randomly divided into 5 groups: blank group, KOA group, warm acupuncture group, BMSCs group, and warm acupuncture combined with BMSCs group. After warm acupuncture combined with BMSCs, the Modified Lequesne MG knee joint assessment scale was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…Among them, warming needle acupuncture is one of the most commonly used methods. Warming needle moxibustion (WNM) is a therapeutic method that combines acupuncture and moxibustion, with efficacy of “channel-warming and cold-dispersing” and “blood-activating and stasis-eliminating” [ 15 , 16 ]. Studies have demonstrated that WNM is one of the primary approaches for KOA treatment in China, and the potential mechanisms might be associated with the deceleration of knee cartilage degeneration [ 17 19 ], the regulation of inflammatory cytokines, and the reduction of algogenic substance release.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, warming needle acupuncture is one of the most commonly used methods. Warming needle moxibustion (WNM) is a therapeutic method that combines acupuncture and moxibustion, with efficacy of “channel-warming and cold-dispersing” and “blood-activating and stasis-eliminating” [ 15 , 16 ]. Studies have demonstrated that WNM is one of the primary approaches for KOA treatment in China, and the potential mechanisms might be associated with the deceleration of knee cartilage degeneration [ 17 19 ], the regulation of inflammatory cytokines, and the reduction of algogenic substance release.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies’ quality scores ranged from 4 to 9 out of 10: one study ( Zhou et al, 2018 ) received a score of 9, eight studies ( Liao et al, 2016 ; Ma et al, 2017 ; Wu et al, 2019 , 2022 ; Wang et al, 2020 ; Jie et al, 2021 ; Liu J. W. et al, 2021 ; Zhu S. Q. et al, 2021 ) received a score of 8, 16 studies ( Xiong et al, 2012 ; Liang et al, 2015 ; Fu et al, 2016a ; Fu et al, 2016b ; Xi et al, 2016 ; Yu, 2016 ; Liu N. G. et al, 2018 ; Wan et al, 2019 ; Zhang et al, 2019a ; Zhang et al, 2019b ; Wang, 2020 ; Chen, 2021 ; Liu H. et al, 2021 ; Zeng et al, 2021 ; Zhu D. Y. et al, 2021 ; Qin et al, 2022 ) received a score of 7, four studies ( Liang, 2015 ; Lin and Xu, 2019 ; Chen et al, 2020 ; Liu D. et al, 2021 ) received a score of 6, three studies ( Wu et al, 2018 ; Liu, 2019 ; Wan et al, 2021 ) received a score of 5, and three studies ( Bao et al, 2011 ; Liu D. et al, 2017 ; Wang D. et al, 2021 ) received a score of 4. There was no research that reported on the sample size calculation.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture can delay KOA progression by modulating p38MAPK and the mitochondrial signaling pathway ( Liao et al, 2016 ; Liu J. W. et al, 2021 ), but the mechanism by which it effects cartilage repair in KOA has not been systematically studied. Systematic review methods facilitate evidence-based clinical decision making ( Ritskes-Hoitinga et al, 2014 ), indicate gaps in research, reduce unnecessary duplication of studies, and support the “replacement, refinement, and reduction of animals” principle in animal research ( Murphy and Murphy, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the epiphyseal blood supply of subchondral bone can also nourish articular cartilage. Studies have shown that when the blood supply around articular cartilage is disturbed, articular cartilage damage may occur, thus showing signs of arthritis [9].…”
Section: Composition Of Blood Vessels Around the Knee Jointmentioning
confidence: 99%